Vertical bone augmentation with guided bone regeneration. A scoping review - Jaime Segovia-Chamorro; Natalia Faúndez-Moreno; Matías Valenzuela-Lezana; Hector Oñate (Universidad de Concepción., 2022)
Introduction: There are multiple techniques for vertical bone augmen-tation. Guided bone regeneration is one of them; however, the literature is diverse and includes different study designs, which makes it difficult to synthesize results. Objective: To analyze the general technical characteristics, clinical results, and complications of vertical bone augmentation performed with guided bone regeneration in humans. Material and Methods: This scoping review was based on the PRISMA-ScR guidelines. A search was performed in the Pubmed, Scielo, and Worldcat databases. Papers published from 1990 to April 2020 were included in the study. Research articles not conducted in humans or published in languages other than English and Spanish were excluded. Title and abstract were screened by two reviewers, then full studies were extracted, and data tabulated. Results: 89 studies were included. The highest percentage reported having obtained a vertical bone increase of less than 5 mm and having used non-resorbable membranes. The most frequent type of graft is autogenous and combinations of grafts, the most common being autogenous with xenograft. All studies that reported bone stability of implants in regenerated bone were favorable, as was implant survival, reporting values between 83.8% and 100%. Membrane exposure is the most frequently reported complication, followed by infection or abscesses, and tissue dehiscence. Conclusion: Vertical bone regeneration is a reliable technique, with high predictability and low incidence of complications compared to other vertical bone augmentation techniques.